Implementation Analysis Of Clinical Pathway At Royal Prima Hospital - Yessica Putri H; Ermi Girsang; Maya Sari Mutia (CV. Inara, 2023)
Clinical pathways are an important part of documents and tools in realizing good clinical governance in hospitals. In Indonesia, this document is also one of the requirements that must be met in the KARS version of the Hospital Accreditation Standard. However, the process of implementing this Clinical Pathway itself also has various problems. Things that might hinder the implementation of this clinical pathway could come from the staff and hospital members themselves because they have not adapted to this Clinical Pathway. This study aims to analyze the implementation of the Clinical Pathway at the Royal Prima Hospital in Medan. This study uses a quantitative design with a cross sectional approach. The research sample was all doctors, nurses, nutritionists, pharmacists at the Royal Prima Hospital Medan who filled the Clinical Pathway as many as 83 people. The results of the Fisher's Exact test showed that there was a significant effect between regulation (p=0.000), compliance (p=0.004), supporting factors (p=0.025), and inhibiting factors (p=0.002). By using the t-test at a significance level of 0.05, the results obtained that regulation is the variable that has the main influence on the implementation of the Clinical Pathway at Royal Prima Hospital Medan (Sig.0.001). Suggestions to hospitals are expected to strengthen policies regarding the implementation of Clinical Pathway to improve health services in hospitals. Caregivers are expected to maintain compliance with the implementation of the Clinical Pathway to improve health services in hospitals.